PERAN MENTORING DALAM MENINGKATKAN KOMPETENSI WIRAUSAHA SYARIAH MAHASISWA DI UNIVERSITAS NEGERI MAKASSAR - sudarmi sudarmi; Mildayanti Mildayanti; Sumiati Tahir; Siti Nardiyah Murhami; Asriyani Amrullah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The development of sharia entrepreneurship in higher education is a crucial strategy for developing independent, competitive, and highly integrated graduates. This article aims to analyze the role of mentoring in enhancing the entrepreneurial competency of sharia students at Makassar State University. The approach used is a literature review with conceptual analysis of mentoring theory, entrepreneurial competency, and sharia economic principles. The results indicate that mentoring plays a significant role in improving entrepreneurial knowledge, skills, and attitudes based on Islamic values. A structured and sustainable mentoring program can strengthen students' self-efficacy, managerial skills, understanding of muamalah jurisprudence, and ethical commitment to running a business in accordance with sharia principles Keywords: mentoring, sharia entrepreneurship, entrepreneurial competency, students, higher education